2015
DOI: 10.1007/s11695-015-1825-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bariatric Surgery Type on Lipid Profile: An Age, Sex, Body Mass Index and Excess Weight Loss Matched Study

Abstract: RYGB is the only bariatric surgery that reduces TC and LDL in age-, sex-, BMI- and EWL-matched patients. All three procedures improved TG and HDL similarly when the confounding effect of weight loss is eliminated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 37 publications
4
24
0
2
Order By: Relevance
“…In addition to patients' BMI and EBW, breath acetone was correlated with several biochemical makers of nutrition and fat metabolism, including concentrations of high-density lipoprotein, neutrophil count, triglyceride, and glucose. These findings are in agreement with existing evidence documenting changes in lipid and glucose metabolism that are associated with obesity and weight loss [2,[22][23][24][25]. Multivariate linear regression revealed that a model incorporating neutrophil count, acetone, low-density lipoprotein and glucose, could predict 41% of the variance in EBW.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition to patients' BMI and EBW, breath acetone was correlated with several biochemical makers of nutrition and fat metabolism, including concentrations of high-density lipoprotein, neutrophil count, triglyceride, and glucose. These findings are in agreement with existing evidence documenting changes in lipid and glucose metabolism that are associated with obesity and weight loss [2,[22][23][24][25]. Multivariate linear regression revealed that a model incorporating neutrophil count, acetone, low-density lipoprotein and glucose, could predict 41% of the variance in EBW.…”
Section: Discussionsupporting
confidence: 90%
“…Multivariate linear regression revealed that a model incorporating neutrophil count, acetone, low-density lipoprotein and glucose, could predict 41% of the variance in EBW. The association of raised neutrophil count, low-density lipoprotein, and glucose with increased BMI/ EBW is well established in the literature [2,22,24]. In the setting of obesity, increased numbers of white blood cells, including neutrophils, are thought to reflect the proinflammatory characteristics associated with this condition and its related comorbidities [24,26].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, it would be advisable to supplement the diet with pyridoxal phosphate, a cofactor of transaminases, and orotic acid, which lowers the concentration of lipoproteins containing apo B. Various reports in the literature concerning lipid profile in bariatric patients indicate that the stabilization of lipid profile occurs after 12 months [6]. There are also reports showing on its significant improvement 2 years after the surgery in 92.3 % of patients and unchanged level of HDL [19].…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 RYGB is a combined malabsorptive and restrictive procedure and it has been shown to induce reductions in serum triglycerides, cholesterol and cholesteryl esters. 12 , 13 , 14 When compared with conventional treatment of obesity, bariatric surgery leads to greater long-term weight loss, higher remission of metabolic syndrome and type 2 diabetes, and decrease in cardiovascular risk. 10 , 15 It is still unclear to what extent the effects of RYGB are related to changes in endogenous metabolism, weight loss or changes in the diet.…”
Section: Introductionmentioning
confidence: 99%